Volume 3: Structures, Safety, and Reliability 2019
DOI: 10.1115/omae2019-96686
|View full text |Cite
|
Sign up to set email alerts
|

Structural Safety Assessment of Marine Operations From a Long-Term Perspective: A Case Study of Offshore Wind Turbine Blade Installation

Abstract: A marine operation is a complex non-routine activity of limited duration carried out in offshore environment. Due to safety reasons, these operations are normally performed within specific sea state limits, which are derived from numerical modelling and analysis of hazardous events. In view of the uncertainties in the assessment of structural responses under stochastic environmental conditions, these limiting curves correspond to a target structural failure probability recommended in offshore standards (for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Please note that in this study, 10 −2 exceedance level is considered, and it corresponds to practical reported incident data in the industry [25] including an acceptable consequence level for the installation task in case of such an event. The categorization of different safety levels and corresponding consequences can be found in [26], and is also discussed briefly in Section 6.5 of this paper.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Please note that in this study, 10 −2 exceedance level is considered, and it corresponds to practical reported incident data in the industry [25] including an acceptable consequence level for the installation task in case of such an event. The categorization of different safety levels and corresponding consequences can be found in [26], and is also discussed briefly in Section 6.5 of this paper.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, wind-turbine blade-mating process, is still a highly demanding task and requires a substantial degree of accuracy [19]. Several bolted connections are present at the blade root, and are required to be docked into the flange holes of the hub [26,27] (Figure 2b). The challenge to the mating operation is due to the considerable relative motions between the blade root and hub which can cause impact loads at the sensitive root connections.…”
Section: Wind-turbine Blade-mating Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Many statistical methods have been used to compute the errors and then be analyzed to find the better fit technique for these calculations. The performance test analysis methods are considered in this study are root mean square error (RMSE), the coefficient of determination (R 2 ), and mean bias error (MBE) and expressed as [16,28,42]…”
Section: Fitness Test Analysismentioning
confidence: 99%